Electromagnetic Signal Attenuation Characteristics in the Lunar Regolith Observed by the Lunar Regolith Penetrating Radar (LRPR) Onboard the Chang’E-5 Lander - Chunyu Ding; Yan Su; Zhonghan Lei; Zongyu Zhang; Mi Song; Yuanzhou Liu; Ruigang Wang; Qingquan Li; Chunlai Li; Shaopeng Huang (Remote Sensing, 2022)
The Chinese Chang’E-5 probe landed in the Mons Rümker of Oceanus Procellarum on the near side of the Moon. The lunar regolith penetrating radar (LRPR) carried by the Chang’E-5 probe allows for the determination of in situ lunar regolith dielectric properties, which are probably related to the age and chemical composition of the regolith. In this paper, we analyze the Chang’E-5 LRPR data with the frequency shift method to estimate the loss tangent of the lunar regolith within a depth of ∼2.8 m. The loss tangent of the Chang’E-5 landing site is constrained to be 0.0148 ± 0.0016, which is substantially higher than that of the typical lunar regolith. The high loss tangent is found to be characteristic of the young basalt age (∼2.0 Ga) and high TiO<semantics>2</semantics>+FeO content (28.21 ± 1.57%) of the Chang’E-5 landing site. Integrated analysis of results from Chang’E-3, Chang’E-4, and Chang’E-5 show that the younger is the geologic age of the mare unit, the greater is the loss tangent of the lunar regolith, and the weaker is the radar electromagnetic signal penetrating ability.